Identity and Marketing Strategies: Lessons Learnt From Indonesian University Websites - Kusuma, Citra Aditya; Abid, Abid (Jambura Science of Management, 2024)
Purpose: Analysing how institutions present themselves on websites provides significant benefits in unravelling the intricacies of the messages educational institutions aim to communicate. In the context of Indonesia, however, there has been limited research on the content of university websites as a promotional tool. Hence, the current study aims to address this void by offering a comprehensive exploration of how educational institutions shape their narratives in the digital era.Design/Methodology/Approach: By adopting a Critical Discourse Analysis (CDA) approach, this study describes the linguistic features of text and images on the websites of the universities located in the Province of Gorontalo, namely Universitas Negeri Gorontalo (UNG) and Universitas Nahdlatul Ulama Gorontalo (UNUGO). A three-dimensional framework developed by Fairclough (2013) was employed for data analysis.Findings: UNG and UNUGO have revealed distinctive strategies in portraying their identities and marketing strategies. UNG adopts a multifaceted approach, incorporating specific historical milestones, official documents, and a symbolic logo philosophy to establish credibility and signal adaptability, while UNUGO strategically positions itself as a reputable Islamic higher education institution, emphasizing religious foundations and academic excellence.